New material from a huge specimen of "Anteophthalmosuchus" cf. "escuchae" (Goniopholididae) from the Albian of Andorra (Teruel, Spain): Phylogenetic implications - Puértolas-Pascual, E.; Canudo, J.I.; Sender, L.M. (Journal of Iberian Geology, 2015)
In 2011 the partial skeleton of a goniopholidid crocodylomorph was recovered in the ENDESA coal mine Mina Corta Barrabasa (Escucha Formation, lower Albian), located in the municipality of Andorra (Teruel, Spain). This new goniopholidid material is represented by abundant postcranial and fragmentary cranial bones. The study of these remains coincides with a recent description in 2013 of at least two new species of goniopholidids in the palaeontological site of Mina Santa María in Ariño (Teruel), also in the Escucha Formation. These species are Anteophthalmosuchus escuchae, Hulkepholis plotos and an undetermined goniopholidid, AR-1-3422. In the present paper, we describe the postcranial and cranial bones of the goniopholidid from Mina Corta Barrabasa and compare it with the species from Mina Santa María. For the first time, we include the taxa from the Escucha Formation in a phylogenetic analysis to establish their relationships within Goniopholididae, adding to what is known of the goniopholidid fossil assemblages from this time interval. The results indicate that the specimen from Mina Corta Barrabasa is closely related to Anteophthalmosuchus escuchae and may be the same species. Together with Hulkepholis plotos and other taxa from England and Belgium, these taxa form an endemic European clade. The Escucha Fm. goniopholidids are the youngest Eurasian members of the group and may be the youngest globally, depending on how North American taxa are eventually resolved.